Metodologi pendidikan TKQ/TPQ - Indra, Hasbi (Ta'dibuna: Jurnal Pendidikan Islam, 2018)
The Quranic Education is a part of a national of education for the better of generation of Indonesian in the global era, they are should ready be generation of Indonesian development. This education has been contact with various changes in the terms of the development of science and technology, ctr. has changes in society increasingly secular, hedonistic and consumeristic and human be a-social and a-morals. These changes should already be predicted by quranic education in order to anticipate the implementation of education. In addition, addressing the issue of quranic education to form a qualified humans that can bring progress in human life. The guidance in terms of quranic education as holy books doctrines comprehensively encourage Muslim to present in the human quality. Quranic education today will face competation era between a country's trade policies. These institutions must adapt in order to prepare the students have bases of knowledge and skills and have good character like discipline, responsibility and so on and students have souls entreprenership for enhance in the following levels and competens in they worlds and made development of nation and deal with its institutions new visions, curriculum and with the best methodological of education.